2000
DOI: 10.1242/jcs.113.6.997
|View full text |Cite
|
Sign up to set email alerts
|

Preferential association of syntaxin 8 with the early endosome

Abstract: Members of the syntaxin family play a fundamental role in vesicle docking and fusion of diverse transport events. We have molecularly characterized syntaxin 8, a novel member of the syntaxin family. The nucleotide sequence of cloned rat cDNA predicts a polypeptide of 236 residues with a carboxyl-terminal 18-residue hydrophobic domain that may function as a membrane anchor. Characteristic of syntaxins, syntaxin 8 also contain regions that have the potential to form coiled-coil structures. Among the known syntax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…However, this may be partly due to overexpression since the native protein is also detectable in endosomes (our unpublished observations). Moreover, in accordance with our data it has recently been reported that vti1b coprecipitates with syntaxin 8 (Subramaniam et al ., 2000) and that endobrevin coprecipitates with syntaxin 7 (Mullock et al ., 2000).…”
Section: Discussionsupporting
confidence: 94%
“…However, this may be partly due to overexpression since the native protein is also detectable in endosomes (our unpublished observations). Moreover, in accordance with our data it has recently been reported that vti1b coprecipitates with syntaxin 8 (Subramaniam et al ., 2000) and that endobrevin coprecipitates with syntaxin 7 (Mullock et al ., 2000).…”
Section: Discussionsupporting
confidence: 94%
“…The syntaxin family belongs to the t-SNARE subfamily of the SNARE superfamily and is involved in vesicle trafficking [ 62 , 63 ]. STX12 is widely expressed and potentially participates in a common trafficking event that occurs in every cell [ 64 66 ], which explains why STX12 showed stable expression levels during early development. The most stable reference gene in different adult tissues was euchromatic histone-lysine N-methyltransferase 1 ( EHMT1 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%